Hypertension Treatment and Control in Older Adult at Tanjung Sari Primary Health Care - Rahmi Fauziah; Enny Rohmawaty; Lazuardhi Dwipa (Althea Medical Journal, 2016)
Background: Hypertension is considered as a major health problem in Indonesia, especially in older adult population because of its prevalence increases by age. Treatment strategy and control management of hypertension in Public Health Center (Pusat Kesehatan Masyarakat, Puskesmas) as primary health care should be enhanced to overcome this issue. This study aimed to describe the pattern of antihypertensive agent in older adults.Methods: This was a descriptive study with total sampling method for data collection. Data were collected from medical record of older adult patients with diagnosis of hypertension at Puskesmas Tanjung Sari from January to December 2013. The variables observed were gender, number of visits, the degree of hypertension, types of antihypertensive drug, combinations of antihypertensive drugs, and blood pressure control.Results: The number of older adults with hypertension was 180 people. Some of which, 120 women (66.7%) participated, 152 (84.4%) had hypertension stage 2, 100 (55.6%) had just one visit, and 80 (44.4%) had more than one visit. Among 80 participants with more than one visit, 8 had achieved target blood pressure. There were 166 participants (92.2%) who received single antihypertensive agent (captopril was given the most), and 14 participants (7.8%) who received the combination of two antihypertensive agent (combination of captopril and HCT (hydrochlorothiazide)) were given the most).Conclusions: More than 75% of older adult with hypertension have stage 2 hypertension and are treated by single antihypertensive agent. Ninety percent of the patient have uncontrolled blood pressure. [AMJ.2016;3(1):17–21] DOI: 10.15850/amj.v3n1.699